2016
DOI: 10.1590/1807-1929/agriambi.v20n2p152-157
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of volume of macaw palm fruit using traditional and the digital Moiré techniques

Abstract: A B S T R A C TThe macaw palm crop has been studied because of its bioenergy potential due to the high oil yield, which is linked to fruit maturity stage. Digital images have been adopted as a contactless way to obtain information about fruit surface area and volume, acting as a sensor for quality control and the classification of fruits, based on physical aspects during the maturation stage. The aim of this study was to estimate the volume of macaw palm fruits from digital models obtained by the Moiré techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
7
1
1
Order By: Relevance
“…Costa et al [13] used the Moiré technique to estimate the volume of macaw palm fruit and compared the Moiré technique to the displacement method of a fluid in order to obtain the volume of the fruit. Lino and Fabbro [14] applied the Moiré technique to obtain the topography of artificial fruit made of paraffin on a 1:1 scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costa et al [13] used the Moiré technique to estimate the volume of macaw palm fruit and compared the Moiré technique to the displacement method of a fluid in order to obtain the volume of the fruit. Lino and Fabbro [14] applied the Moiré technique to obtain the topography of artificial fruit made of paraffin on a 1:1 scale.…”
Section: Resultsmentioning
confidence: 99%
“…The authors obtained a digital model of pears through the Moiré technique and compared it to the three-dimensional model obtained through a laser scanner. In both cases [13,14], the authors found a good correlation between the three-dimensional model obtained through the Moiré technique and the comparison methods, which were volume displacement of a fluid [13] and the 3D model obtained through a laser scanner [14].…”
Section: Resultsmentioning
confidence: 99%
“…The longitudinal and transverse diameter of the fruits were measured with the aid of a stainless steel digital caliper (brand Stainless Hardened). The volume was estimated by the water displacement method, by initially immersing five blackberry fruits in a graduated cylinder containing 100 mL of water and recording the difference between volume before and after fruit immersion (Costa et al, 2016). The fruits of each block were harvested for the determination of yield and estimated productivity of the fruits, being weighed using a semi-analytical digital scale (model N0 4052E, brand LUXOR).…”
Section: Methodsmentioning
confidence: 99%
“…Many researches in estimation of fruits' weight using 2D images used Regression as learning method to estimate fruits' weight from its pre-determined volume. It has shown good accuracy in estimating weight of apple, sweet-lime, lemon and orange [7] with R 2 > 0.86 and macaw palm fruits [8] with R 2 of 0.837. Other research estimated weight of apples using Linear Regression based on its diameter and area and show accuracy of 96.5% [9].…”
Section: Introductionmentioning
confidence: 99%